The Effect of Abdominal Stretching Exercises On Reducing Menstrual Pain In Adolescent Girls At Mts Bina Insani Kecamatan Raya Kahean Kabupaten Simalungun 2021 - Ferika Desi (Institute of Computer Science (IOCS), 2021)
Adolescence is a period of change both physically, biologically, and productively. Adolescence begins when a person experiences changes both physically, biologically and reproductively. In adolescent girls, the most prominent thing when experiencing growth and development, one of which is menstruation (menstruation). Adolescent women who experience menstruation is something physiological and normal. Several risk factors related to the severity of dysmenorrhea symptoms are younger age at the time of menarche, longer menstrual periods, the amount of blood that comes out during menstruation, smoking, family history of dysmenorrhea, obesity and alcohol use are also associated with the occurrence of primary dysmenorrhea.. This research aims todetermine the effect of abdominal stretching exercises on the reduction of menstrual pain in adolescent girls in MTs. Bina Insani Kec. Raya Kahean Kab. Simalungun Year 2021. The type of research used is Pre-Experimental research with one group pre-post test design. The population in this study were all adolescent girls in grades 1,2,3 who experienced dysmenorrhea in MTs. Human Development. The sampling technique used Accidental Sampling with a sample size of 20 people. Data collection using the Numeric Paint Rating Scale (NRS) instrument. Data analysis used the Wilcoxon test with a significant level of p<0.05). The results of the analysis show that there is an effect of abdominal stretching on the intensity of dysmenorrhea pain in adolescent girls at MTs Bina Insani Kec. Raya Kahean Kab. Simalungun with a value of P = 0.001 where P = <0.05. It is suggested that this research can be used as information for young women in MTs. Bina Insani Kec. Raya Kahean Kab. Simalungun as a non-pharmacological management to treat dysmenorrhea pain experienced by adolescent girls.